ANIME DAN PERSEPSI BUDAYA KEKERASAN PADA ANAK USIA SEKOLAH - Andina, Elga (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
The rising number of violence and bullying cases between studentis worrying. Some people accused violence anime as the cause. However, violence anime shows not only aggression acts, but also delivering positive values needed by children. Data from anime forums suggests such animes deliver ideas kind of like: hard working, never give up, altruism, and solidarity. This means violence acts among school age children may derive from other variables.